Limited utility of novel serological biomarkers in patients newly suspected of having giant cell arteritis. (13th April 2021) - Sammel, Anthony M.; Xue, Meilang; Karsten, Elisabeth; Little, Christopher B.; Smith, Susan; Nguyen, Katherine; Laurent, Rodger
Abstract: Aim: Diagnosing and monitoring vascular activity in giant cell arteritis (GCA) is difficult due to the paucity of specific serological biomarkers. We assessed the utility of 8 novel biomarkers in an inception cohort of newly suspected GCA patients. Method: Consecutive patients were enrolled between May 2016 and December 2017. Serum was collected within 72 hours of commencing corticosteroids and at 6 months. It was analyzed for levels of intra‐cellular adhesion molecule 1, vascular endothelial growth factor (VEGF), pentraxin 3, von Willebrand factor and procalcitonin (5‐plex R&D Systems multiplex assay) and interleukin (IL)6, IL12 and interferon‐γ (high‐sensitivity 3‐plex ProcartaPlex multiplex assay). A GCA specific positron emission tomography / computed tomography (PET/CT) scan was performed at enrolment with uptake in each vascular territory graded and summed to derive a total vascular score (TVS). Results: For the 63 patients enrolled, 12 (19%) had a final diagnosis of biopsy‐positive GCA and a further 9 had a clinical diagnosis of biopsy‐negative GCA. None of the 8 biomarkers was significantly higher in GCA patients compared with those with alternative diagnoses, or demonstrated a positive correlation with the PET/CT TVS. This was in contrast to the C‐reactive protein (CRP) and erythrocyte sedimentation rate (ESR) which were higher in the biopsy‐positive GCA cohort ( P < .04) and showed weak positive correlations with the TVS (correlation coefficient 0.34, P < .01). Procalcitonin did not distinguish between GCA and infection. Concentrations of CRP, ESR, VEGF and pentraxin 3 decreased between diagnosis and 6 months in GCA patients. Conclusion: This study did not identify new serological biomarkers to assist in diagnosing or assessing the vasculitis burden in GCA.